Technology’s application in the implementation of total quality management at hail university: Insights from department heads - Ali Almutlaq, Majed; Ali H Alshammari, Thani (Edelweiss Applied Science and Technology, 2024)
This quantitative study examined the perspectives of departmental managers on the role of technology in the implementation of total quality management (TQM) at Hail University in Saudi Arabia. A sample of 60 departmental heads (36 men and 24 women) completed a two-part questionnaire. The questionnaire sought the demographic details of respondents, their thoughts on the utility of TQM in higher education in general, the role of technology in TQM implementation, the efficacy of TQM in achieving the Saudi Vision 2030, and the application of technology in the seven TQM principles as defined by the Baldrige-Education Criteria for Performance Excellence (NIST, 2004). According to the findings, technology is an extremely important component of the Total Quality Management (TQM) program at Hail University. Most of the department heads concluded that implementing TQM in the environment of the university is not only highly successful but also has the potential to help increase organizational performance. Furthermore, the study concluded that TQM implementation has become an important aspect of the field of education. This is because it significantly improves the university’s administration and management efficiency. This study also discovered significant differences in how Hail University department heads used technology to implement TQM. Overall, females outperformed males, and younger people outperformed older people.